MANAGING THE STRATEGIC DEVELOPMENT OF THE TRANSPORT SECTOR ENTERPRISES IN TERMS OF GLOBALIZATION CHALLENGES - SAKUN, Lesia; VIELKIN, Bohdan (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article is devoted to the latest methods used to manage the strategic development of transport enterprises in the context of globalization challenges. Steady functioning of transport enterprises contributes to the sustainable economic growth of our country. Among the biggest globalization challenges in recent years for the world economy, and particularly for Ukraine, have been the Coronavirus pandemic and hostilities with the Russian Federation. Motor transport has been and remains extremely important, along with rail transport, especially during the epidemic and the war. The article covers the dynamics of the share of freight / passenger turnover and transported goods / passengers by transport in Ukraine over the period of 2016-2021. The growth of the share of freight turnover - from 16.9% in 2016 to 22.4% in 2021; the share of transported goods - from 70.45 to 76.6%, respectively, characterizes the high competitiveness and high market potential of road transport enterprises in the Ukrainian freight market.Major problems, which should be guided by the development strategy of passenger transport enterprises of Poltava region, are explored: improving the quality of transport services for the population by updating the rolling stock of enterprises; improving the safety of transportation and reducing the negative impact on the environment; optimization of the population's expenditures on passenger transportation. Strategic guidelines for the development of the transport system of Poltava region have been formulated. The factors that cause considerable changes in the dynamics of transport deliveries were analyzed. Transportation of humanitarian cargoes became a priority. Because of the war, the efficiency of using the transit potential of the country has significantly decreased. Military actions against the Russian Federation do not allow to fully use the strategic advantages of the Black Sea-Azov region, the total cargo turnover of which is more than 200 million tons per year. Moreover, 2714.5 km of water navigable arteries are not effectively used. Thus, river transport may be one of the strategic directions of development of the transport industry in the conditions of war and fuel crisis.
Keywords: globalization challenges; strategic development; transport industries; motor transport; passenger turnover; cargo